Benign cutanous Degos' disease: A case report and review of the literature - Coskun, B; Saral, Y; Cicek, D; Ozercan, R (Wiley, 2004)
We report a case of benign form of Degos' disease, a rare condition often characterized by multisystemic vasculopathy, and discuss the case by the light of the limited literature available. A 34-year-old male patient was admitted to our clinic with lesions on his neck and back and a history of not getting any benefit from previous acne medications. Dermatological examination revealed erythematous papules with hemorrhagic crusts on their surfaces and many well-defined atrophic scar tissues. Histopathological evaluation of a biopsy obtained from a lesion revealed the findings of Degos' disease. Further evaluation did not reveal any sign of systemic involvement. He was diagnosed with the benign form of Degos' disease.
Keywords: Degos' disease (malign atrophic papulosis); benign cutaneous Degos' disease